Analisis Strategi Pemasaran di Era Digital Untuk Membangun Loyalitas Pelanggan - Achmad Fauzi; Nurul Syah Nasyid Firdauzy; Ernita Shafa Nur Fadhilah; Muhammad Syah Naufaly Aziz; Nurul Fauzia; Puspita Ayu Maharani; I Putu Dananjaya Krisna; Ridho Riyanto (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In a highly competitive environment, a proper marketing strategy is needed to increase the number of customers. The marketing process must be properly managed so that it can respond promptly and meet the needs and demands of customers. Digital technology has changed the way people act, speak, and make decisions. Your digital marketing strategy should align with your business strategy. First, attract customers with deals and discounts. This research uses a qualitative approach that focuses on observations in detail.